Tearsucker [videorecording (DVD)] - Brittan, Sam; Brittan, Sam; Walter, Allison; Yetter, Emily; Spisso, Danielle McRae (Freestyle Digital Media, 2023)
Lilly, an emotionally vulnerable trauma survivor, is desperate to heal and get on with her life. Despite the support of her best friend Deb, she feels completely isolated. Every day is the same thing she just can't stop crying. When she crosses paths with a charming stranger, Tom, at the park, she feels hope for the first time in months. Her luck may finally be turning around. Tom is kind, attentive, and supportive. Tom sweeps Lilly off her feet, and invites her on a romantic weekend getaway however, Tom has an unusual appetite for tears and will stop at nothing to get them.